Page_123otherMemorializing an Ideal: Representations of Inclusivity in Canada's National Public Monuments. Issue 1 (14th November 2019) - Weeks, Eric
Abstract : In every corner of every town and city, memorials can be found existing in a variety of forms and serving a variety of functions. From small plaques or roadside markers to grand monuments commemorating a national or global event, they attempt to remind the public of individuals or a shared history. However, memorials also perform another role, and that is to not only record and display those subjects which a society deems worthy of commemoration, but also how those histories are shaped, framed and positioned to fit contemporary needs. This paper examines the use of memorials and monuments within Ottawa to create and demonstrate an inclusive, diverse and welcoming Canada. These values are found throughout Canadian society but looking at Ottawa's built environment – the additions to the landscape created from steel and granite – reveals a deeper understanding of what these ideals mean to Canadians, how the nation sees itself and how it portrays itself to the world.